Vegetative propagation of hops (Humulus lupulus), effect of biostimulants, size and position of cuttings - Brighenti, Luiz Humberto Mattos; Sautchuck , Sabrina; Malohlava, Isadora Teixeira Coelho; Votre, Thainá Carolina Graciano; Pinto, Felipe Augusto Moretti Ferreira; Brighenti, Alberto Fontanella; Pescador, Rosete; Felini, Victoria Silva (Revista de Ciências Agroveterinárias, 2023)
The aim of this work was to evaluate the effect of different cutting lengths, the use of biostimulants and diameter of cuttings on hops vegetative propagation. The work was conducted in a greenhouse at the Center for Agricultural Sciences (CCA) at the Federal University of Santa Catarina (UFSC), in Florianópolis/SC, Brazil, between October 2019 and January 2021. In experiment 1, cuttings with one, two and three buds were tested, with and without application of biostimulant SprintAlga TS® (Biolchim) in Brewer’s Gold and Cascade cultivars. In experiment 2, cuttings with diameter of 1.5 cm, 2.5 cm and 3.5 cm were tested for Northern Brewer cultivar. In both experiments, survival, rooting, root length, root quality, number of shoots and shoot length were evaluated. In experiment 1, Cascade had lower survival, rooting and development compared to Brewer’s Gold. The use of biostimulant increased survival and rooting rates of both cultivars. For Brewer’s Gold the use of biostimulant improved root quality and increased shoot number, root and shoot length. For Brewer’s Gold, 3-bud cuttings improved root quality and increased number of shoots. For Cascade, 1-bud cuttings showed the highest survival, rooting and development rates. In experiment 2, the highest rates of survival, rooting and the longest root length were obtained with 1.5 cm diameter cuttings. Larger diameter cuttings (2.5 and 3.5 cm) produced fewer shoots, but longer shoots.